Jubileusz 160-lecia nauk rolniczych w Puławach – Wiesław Oleszek, Teresa Doroszewska, Mariusz Matyka, Stanisław Krasowicz - Oleszek, Wiesław; Doroszewska, Teresa; Matyka, Mariusz; Krasowicz, Stanisław (Polish Journal of Agronomy, 2021)